Literacy and Nationalization of Italian Children in Brazil - Teixeira Corrêa, Rosa Lydia (2018)
The following article discusses aspects of Italian nationalization found in two primary education textbooks in Brazil, which were used in Italian schools in this country. It analyses how the ideal of an Italian nation was instilled in Italian elementary school students in Brazil at the beginning of the 20th century, through many references to figures such as the queen mother, kings, and Italian national heroes. It also highlights the reactions to such inculcation methods from many sectors of Brazilian society.